2010
DOI: 10.1287/mnsc.1100.1146
|View full text |Cite
|
Sign up to set email alerts
|

Contracting for Collaborative Services

Abstract: In this paper, we analyze the contracting issues that arise in collaborative services, such as consulting, financial planning, and IT outsourcing. Analyzing first a bilateral relationship, we assume that neither the buyer's nor the vendor's efforts are directly observable, resulting in double moral hazard. We investigate the efficiency of fixed-fee, time-and-materials, and performance-based contracts. We find that fixed-fee contracts are the least responsive to unplanned contingencies, time-and-material contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(134 citation statements)
references
References 50 publications
3
131
0
Order By: Relevance
“…While Roels et al 2010 have pointed to this theoretical possibility, currently no empirical evidence exists to support it. In fact, Guajardo et al 2012, in an empirical study of aircraft engine maintenance, showed evidence to the contrary, i.e., having the service provider assume responsibilities for both equipment failure and repair costs leads to less failure events.…”
Section: Discussionmentioning
confidence: 99%
“…While Roels et al 2010 have pointed to this theoretical possibility, currently no empirical evidence exists to support it. In fact, Guajardo et al 2012, in an empirical study of aircraft engine maintenance, showed evidence to the contrary, i.e., having the service provider assume responsibilities for both equipment failure and repair costs leads to less failure events.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our setup also captures some key decentralization issues from the service outsourcing literature related to service quality, capacity building, utilization, etc. (Ren and Zhang (2009);Roels et al (2010) (2) Mediated Sourcing: Both buyers source through a third party, the Intermediary. The intermediary allocates business and acts for both buyers in the transaction step.…”
Section: The Transactionmentioning
confidence: 99%
“…Such an "unbundling" view neglects contributions by the partners that cannot be defined as a part of the project, for example, improvements in efficiency due to knowledge spillovers through collaboration. Differently, this paper approaches PPP from the perspective of the theory of contracting for collaborative projects (Roels et al, 2010; Kim and Netessine, 2013; Roels, 2014) to identify the specific advantages 4 brought by a partnership as compared to contracting out and other forms of collaboration between the public and the private sector.…”
Section: Introductionmentioning
confidence: 99%
“…Information frictions imply welfare losses due to verification costs. Roels et al (2010) study the problem of contracting for collaborative services under asymmetric information. They derive optimal types of contracts depending on the elasticity of project outcomes to contributions of the collaborating parties.…”
Section: Introductionmentioning
confidence: 99%